(untitled) (Fiep Bulletin - online, 2013)
Taekwondo is recent in the Olympics, resulting in little knowledge about its preparation, development and profile of the successful athletes. The aim of this study was to compare and to analyze the height and age of Taekwondo athletes medalists (MED) and non-medalists (NMED) and to analyze the characteristics of the Olympics fighting in Sydney and Beijing. The sample consisted of 102 fighters in Sydney and 128 in Beijing. The following characteristics were studied for athletes: weight division, height, age and country of origin. The fights was analyzed in the following topics: penalties, points of kick and punch, points of attack (AT) and counterattack (CAT), final score of each fight. All data were captured in the official internet site of Olympics, and were analyzed using descriptive statistics and analysis of variance. It was found that in Sydney the age of men and women MED was lower than NMED; in Beijing happened the opposite. However, in both is not obtained significant difference between MED and NMED (p> 0.05). The average height of athletes showed no significant difference for MED and NMED in Sydney (p>0,05); in Beijing there was significant difference for some weight divisions. In Sydney the AT represented 52% of all the valid points, while in Beijing the CAT accounted for 55.63%. The punches were 2% in Sydney and Beijing in 0.28% of all points. In Sydney there was not the decision of tie through the golden point (GP), but in Beijing 45.45% of the GP decisions were by a CAT point. In Sydney the majority part of penalties occurred in the first round, while in Beijing it was in the third, both mainly by winner. It was concluded that the height and age does not influence the achievement of medals, the CAT was more efficient to score, the penalties have been committed mainly by the winner of the fight and punch is becoming less used.